2020
DOI: 10.3390/rs12132172
|View full text |Cite
|
Sign up to set email alerts
|

An Algorithm to Estimate Suspended Particulate Matter Concentrations and Associated Uncertainties from Remote Sensing Reflectance in Coastal Environments

Abstract: Suspended Particulate Matter (SPM) is a major constituent in coastal waters, involved in processes such as light attenuation, pollutant propagation, and waterways blockage. The spatial distribution of SPM is an indicator of deposition and erosion patterns in estuaries and coastal zones and a necessary input to estimate the material fluxes from the land through rivers to the sea. In-situ methods to estimate SPM provide limited spatial data in comparison to the coverage that can be obtained remotely. Oce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 58 publications
1
23
0
Order By: Relevance
“…The strong fit between the Novoa and the Wen algorithms suggests that the switch of band and criteria of the Novoa algorithm allows the algorithm to be more flexible to different TSS levels since the algorithm integrates different bands and was tested with a wide TSS dataset (2.6–1579 mg/L). Balasubramanian et al, 2020 , Tavora et al, 2020 compared several TSS-estimate algorithms and both achieved good results for the Novoa algorithm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The strong fit between the Novoa and the Wen algorithms suggests that the switch of band and criteria of the Novoa algorithm allows the algorithm to be more flexible to different TSS levels since the algorithm integrates different bands and was tested with a wide TSS dataset (2.6–1579 mg/L). Balasubramanian et al, 2020 , Tavora et al, 2020 compared several TSS-estimate algorithms and both achieved good results for the Novoa algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…The underestimation of Nechad (R) and Nechad (G) probably results from the relatively narrow TSS range of the in-situ data used for testing the algorithm (1.24–110.27 mg/L), which may have caused the saturation as TSS concentration rise. Tavora et al (2020) indicated that the reflectance in the visible spectral region could suffer from saturation in high TSS water conditions. In this Min River case, the Nechad (R) algorithm performed quite well in relatively low TSS concentration waters but not so well in high TSS waters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The estimated uncertainties for Han et al (2016) and Dogliotti et al (2015) are found to be much higher, especially in relatively clear waters. The Tavora et al (2020) algorithm is a semi-analytical approach; the relatively large uncertainties found here could be related to the default band setting considered (which only used the red and NIR bands) and the differences between the optical parameters used (e.g., the mass-specific absorption coefficients) and their true values. Both the Novoa et al (2017) andD'Sa et al (2007) algorithms are subject to larger uncertainties than those from the NIR-RGB algorithm.…”
Section: Comparison With State-of-the-art Algorithmsmentioning
confidence: 99%